Asuhan Keperawatan Jiwa Pada Pasien Gangguan Persepsi Sensori Halusinasi Dengan Pemberian Terapi Musik Klasik di Yayasan Rehabilitasi Mental Griya Bakti Medika - Titi Sabariyah; Ayu Pratiwi; Mentari Mentari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Mental disorders are a description of a syndrome with a variety of causes, many of which are not yet known with certainty and the course of the disease is not always chronic, in general it is characterized by fundamental deviations, characteristics of thoughts and perceptions, as well as the presence of unnatural or blunted affect. One of the mental disorders that occurs is sensory perception disorder: hallucinations. Hallucinations are a loss of human ability to differentiate between internal stimuli (thoughts) and external stimuli (outer world). How to treat hallucinations can be done in pharmacological and non-pharmacological forms. One non-pharmacological therapy that is effective in reducing hallucinations is music therapy. Method: Giving classical music listening therapy to patients for 4 days is carried out 1 day once therapy for 10-15 minutes. Results: Classical music activity therapy nursing intervention greatly influenced the level of hallucinations in patients with hallucinatory auditory sensory disorders. Conclusion: Providing classic music therapy can help reduce the frequency of hallucinations. This is due to the diversion of the patient's attention from the hallucinatory sounds to the classic music he hears. rebuking and music to reduce the symptoms of the hallucinations he was suffering from.